Current and future availability of and need for human resources for sexual, reproductive, maternal and newborn health in 41 countries in Sub-Saharan Africa - Maria Guerra Arias; Andrea Nove; Michaela Michel-Schuldt; Luc de Bernis (BMC, 2017)
Abstract Background The WHO African region, covering the majority of Sub-Saharan Africa, faces the highest rates of maternal and neonatal mortality in the world. This study uses data from the State of the World's Midwifery 2014 survey to cast a spotlight on the WHO African region, highlight the specific characteristics of its sexual, reproductive, maternal and newborn health (SRMNH) workforce and describe and compare countries' different trajectories in terms of meeting the population need for services. Methods Using data from 41 African countries, this study used a mathematical model to estimate potential met need for SRMNH services, defined as "the percentage of a universal SRMNH package that could potentially be obtained by women and newborns given the composition, competencies and available working time of the SRMNH workforce." The model defined the 46 key interventions included in this universal SRMNH package and allocated them to the available health worker time and skill set in each country to estimate the potential met need. Results Based on the current and projected potential met need in the future, the countries were grouped into three categories: (1) 'making or maintaining progress' (expected to meet more, or the same level, of the need in the future than currently): 14 countries including Ghana, Senegal and South Africa, (2) 'at risk' (currently performing relatively well but expected to deteriorate due to the health workforce not keeping pace with population growth): 6 countries including Gabon, Rwanda and Zambia, and (3) 'low performing' (not performing well and not expected to improve): 21 countries including Burkina Faso, Eritrea and Sierra Leone. Conclusion The three groups face different challenges, and policy solutions to increasing met need should be tailored to the specific context of the country. National health workforce accounts should be strengthened so that workforce planning can be evidence-informed.